Answer:0.013353877
Explanation:
3^(2x+1)-18^(3x)-81=0. follow PEMDAS. perenthesis, exponents, */+-
3^2=9 and 3^1 = 3, so
9x+3-18^(3x)-81=0
18^3= 5832, so
9x+3-5832x-81=0
9x+5832x= 5841x, because combining the like terms helps you narrow down an equation with two variables
5841x+3-81=0
0-3+81=78, because you need to try to isloate x. when you bring it to the other side of the equal side, the + turns into a - and a - turns into a +
5841x=78
x= 78/5841
x= 0.013353877
please let me know if i am making a mistake